Characteristics of U.S. Baccalaureate Health Informatics Programs - McCarthy, Katie A.; Eldredge, Christina; Mercado, Fatima; Wong, Anya; Gajjar, Rohan (Applied Clinical Informatics, 2024)
Background Health informatics (HI) is a growing field of study, yet sparse data are available on the characteristics of undergraduate HI programs in the United States. The lack of a central location for U.S. HI undergraduate program data has led to a gap in information to support current efforts to promote academic standards in the field and attract potential students.Objectives The objective of this study was to perform an environment scan of colleges and universities within the United States and Puerto Rico to identify undergraduate programs in HI including majors, minors, and undergraduate-level certificates.Methods Potential institutions offering HI programs were identified from the National Center for Education Statistics (NCES), the Commission for Accreditation of Health Informatics and Health Information Management Education (CAHIIM), the Association of University Programs in Health Administration (AUPHA), the Healthcare Information and Management Systems Society (HIMSS), and the American Health Information Management Association (AHIMA). Publicly available materials for these institutions were reviewed, and data were captured for identified HI programs including geographic location; college or school in which the program was offered; type of degree (if applicable); program title; total credits to complete the program; delivery format; and source of data.Results A total of 83 HI programs were identified from 60 institutions and 26 states. The primary finding of this environment scan was that inconsistencies exist among U.S. HI undergraduate programs including variations in offering college/school, title of program, number of credits required, delivery formats, CIP codes, and the type of information published on university/college websites.Conclusion This environment scan was a first step in exploring the characteristics of undergraduate HI programs within the United States. Further research is needed on the curricular similarities and differences among the programs, the administrative methods of these interdisciplinary programs, and the information most needed by current and potential undergraduate students.
Keywords: clinical informatics; workforce; accreditation; process improvement